Urgent neurosonological examinations during COVID-19 pandemic - Valaikienė , J. (Neurologijos seminarai, 2020)
The pandemic of coronavirus disease 2019 forced to create urgent medical safety diagnostic protocols to limit the spread of this deadly infection. The article presents the indications, safety requirements, techniques, and clinical examples of neurological point-of-care ultrasonography or neuro-POCUS. The importance and limitations of the neuro-POCUS are discussed.
Keywords: POCUS; ultrasound; COVID-19 pandemic; urgent diagnostics; color duplex sonography; stroke